Transcribing Complexes in Cells Infected by Vesicular Stomatitis Virus and Rabies Virus - Villarreal, Louis Perez (1974)
We analyzed cell extracts from BHK(21) cells infected with vesicular stomatitis virus (VSV) and rabies virus for in vitro RNA polymerase activity. Cells infected with VSV B virions exhibited several complexes with in vitro RNA polymerase activity in sucrose gradients. These complexes synthesize VSV transcriptase product (4 to 18S) polyadenylated in RNA complementary to virion RNA. Cells infected with a high multiplicity of B virions and T particles show only one RNA polymerase complex active in vitro. This complex sediments at 110S and makes only small (2S) RNA. Carrier BHK(21) cells persistently noncytopathically infected with VSV contain several complexes active in RNA polymerase, but both exhibit very low activity. Cytoplasms of cells noncytopathically infected with rabies virus also show very low levels of a complex containing RNA polymerase activity. No transcriptase nor any other in vitro polymerase activity could be found associated with purified rabies virions, although they do carry out primary transcription in cells treated with actinomycin D and cycloheximide before infection.